Enterprise resource planning’s adoption model in public sector organizations - Zainol, Zaini; Ahmad @ Abdul Mutalib, Hawa (2019)
The introduction of enterprise resource planning (ERP) system as a tool to increase performance has encouraged many organizations to adopt it. This includes the public sector organization (PSO) that adopted a more effective system to deliver a more efficient citizen-centric services and enhance operational proficiencies. Even though the government should strive for improvement via the adoption of ERP, organizations might not benefit from these enhancement. The aim of this study is to investigate the impact of the ERP system upon PSO’s performance in Malaysia using the DeLone and McLean Information System (IS) success model and four perspectives of Balanced Scorecard (BSC) measurement model, which are financial, customer, internal business, and innovation and learning. This study presents evidence, gathered from a questionnaires survey of 52 local authorities (LAs) in Malaysia that have implemented the system. The data were collected by an electronically distributed Google Form questionnaire. The findings indicated that system quality is positive as predicted and significant for all perspectives of BSC. It is also found that the information quality is positively related and significant towards the customer perspective, and positively related but not significant towards the financial, internal business, and innovation and learning perspective in Malaysia. It was also proven that a good quality system supporting user performance is related to the net benefits gained, leading to a positive impact for all perspectives of BSC. The results also ascertained that the implementation of ERP system in LA organizations leads improved performance, proving the suitability of the system vis-à-vis the PSO. The results are expected to encourage other PSOs to adopt a similar strategy in order to gain benefits similar to ones enjoyed by LAs